Sowing time matters: Advancing rice and wheat sowing shape system productivity - Srivastava, Amit; Patil, Vikram; Peramaiyan, Panneerselvam; Kumari, Tanu; Munshi, Sugandha; Veettil Chellattan, Prakashan; Urfels, Anton; Poonia, Shispal; Kumar, Anurag; Kumar, Pankaj; Ignatius, Moben; Challa, Kranthi Kumar; et al. (2025)
Timely sowing is a decisive factor shaping the productivity of rice–wheat systems (RWS) across the eastern Indo-Gangetic Plains, where delays in Kharif rice often cascade into late Rabi wheat planting and increased exposure to terminal heat. This study examined how shifts in sowing windows influence crop and system-level yields in seven districts of Bihar using two years of field data (2022–23 and 2023–24), satellite-derived planting dates, NDVI dynamics, and multivariate statistical analyses. Early sowing consistently improved yields of both crops, by 0.7–0.9 t/ha in rice, 0.5–0.6 t/ha in wheat and increased total system productivity by roughly 1.4 t/ha. Temperature analysis showed that late-sown wheat was exposed to 12–15 days with mean temperatures above 30°C during grain filling, aligning with yield declines of about 0.05 t/ha per day of sowing delay beyond 15 November. PCA revealed that early sowing reduced variability across LDV, MDV and SDV , while late sowing increased dispersion, particularly in LDV . MANOVA identified sowing time as the strongest driver influencing satellite-based NDVImax and yield, surpassing district, variety, or year effects. Satellite-derived planting maps further confirmed the spread of late sowing across districts in 2023, reinforcing its role in system-wide productivity losses. Building on these insights, a minimum viable product (MVP) advisory framework, transitioning from verbal advisories to the AgDay digital decision- support platform was piloted to promote timely sowing. The study provides actionable thresholds and systematic evidence to support scalable, climate-smart advisories capable of strengthening the resilience of rice–wheat systems under rising temperature risks.